The Mast Cell Degranulator Compound 48/80 Directly Activates Neurons - Schemann, Michael; Kugler, Eva Maria; Buhner, Sabine; Eastwood, Christopher; Donovan, Jemma; Jiang, Wen; Grundy, David (PLOS ONE, 2012)
Background Compound 48/80 is widely used in animal and tissue models as a “selective” mast cell activator. With this study we demonstrate that compound 48/80 also directly activates enteric neurons and visceral afferents. Methodology/Principal Findings We used in vivo recordings from extrinsic intestinal afferents together with Ca++ imaging from primary cultures of DRG and nodose neurons. Enteric neuronal activation was examined by Ca++ and voltage sensitive dye imaging in isolated gut preparations and primary cultures of enteric neurons. Intraluminal application of compound 48/80 evoked marked afferent firing which desensitized on subsequent administration. In egg albumen-sensitized animals, intraluminal antigen evoked a similar pattern of afferent activation which also desensitized on subsequent exposure to antigen. In cross-desensitization experiments prior administration of compound 48/80 failed to influence the mast cell mediated response. Application of 1 and 10 µg/ml compound 48/80 evoked spike discharge and Ca++ transients in enteric neurons. The same nerve activating effect was observed in primary cultures of DRG and nodose ganglion cells. Enteric neuron cultures were devoid of mast cells confirmed by negative staining for c-kit or toluidine blue. In addition, in cultured enteric neurons the excitatory action of compound 48/80 was preserved in the presence of histamine H1 and H2 antagonists. The mast cell stabilizer cromolyn attenuated compound 48/80 and nicotine evoked Ca++ transients in mast cell-free enteric neuron cultures. Conclusions/Significance The results showed direct excitatory action of compound 48/80 on enteric neurons and visceral afferents. Therefore, functional changes measured in tissue or animal models may involve a mast cell independent effect of compound 48/80 and cromolyn.